PENGARUH TINGKAT PENDIDIKAN, KEMAMPUAN PERSONAL, PENGALAMAN KERJA TERHADAP EFEKTIVITAS SISTEM INFORMASI AKUNTANSI LEMBAGA PERKREDITAN DESA KECAMATAN DENPASAR TIMUR - I Gede Fajar Novyar Danuarta; I Putu Gde Chandra Artha Aryasa; Gede Sanjaya Adi Putra (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Warmadewa, 2026)
This study examines in depth how educational background, individual competencies, and work experience influence the performance of accounting information systems in Village Credit Institutions (LPD) in the East Denpasar District. The effectiveness of this system serves as a key foundation for navigating the institution’s strategic decision-making. The main assumption points to the quality of human resources as a determining factor in the system’s success, particularly in terms of intellectual capacity, personal skills, and work experience. Using a quantitative approach, data were collected through questionnaires distributed to 48 respondents and analyzed using multiple linear regression. The results show that all three factors significantly contribute to the functionality of the system. These findings underscore that improving employees' cognitive and operational capabilities is a fundamental step in strengthening the accounting information system within LPDs. Investing in human resource development is not merely supplementary—it is the core of a competitive digital accounting transformation.